Ileum preserving expanded jejunectomy and pancreaticoduodenectomy with combined resection of the superior mesenteric artery for huge retroperitoneal solitary fibrous tumor. Issue 8 (22nd June 2017) - Egashira, Akinori; Ikeda, Yasuharu; Morita, Masaru; Taguchi, Ken‐ichi; Kinjyo, Nao; Tsujita, Eiji; Minami, Kazuhito; Yamamoto, Manabu; Toh, Yasushi
Key Clinical Message: We encountered a patient with a large retroperitoneal solitary fibrous tumor, in whom we could preserve approximately 150 cm of the ileum even after pancreaticoduodenectomy combined with resection of the superior mesenteric artery, thus preventing short bowel syndrome. Abstract : We encountered a patient with a large retroperitoneal solitary fibrous tumor, in whom we could preserve approximately 150 cm of the ileum even after pancreaticoduodenectomy combined with resection of the superior mesenteric artery, thus preventing short bowel syndrome.